An Educational Test Rig for Kinesthetic Learning of Mechanisms for Underactuated Robotic Hands - Gabriele Maria Achilli; Silvia Logozzo; Maria Cristina Valigi (Robotics, 2022)
Teaching robotics requires interdisciplinary skills and a good creativity, providing instructions and hands-on experiences, exploiting different kinds of learning. Two kinds of learning methods are commonly used: the ‘visual learning’ and the ‘auditory learning’, recognizable by the preference of an approach for images, rather than for texts, or oral explanations. A third possible learning style is the ‘kinesthetic learning’, based on tactile activities, which is generally least exploited, both by teachers in the classroom and by students during individual study. In this perspective, the use of educational test rigs is a good practice and adds an opportunity to share a passion for robotics. The paper focuses on the realization and application of an educational test rig aimed at explaining how a differential mechanism works and how it can be applied to robotic underactuated soft grippers to move multiple robotic fingers independently of each other using just a single actuator. The differential test bench was realized by 3D printing and mounted with the help of students in high school seminaries oriented to encourage students towards robotic or mechatronic studies. This activity was very thrilling for the students and helped them to approach robotics in a natural way, exploiting kinesthetic learning as it is demonstrated by test results.